The influence of the preparation method of NiOx photocathodes on the efficiency of p-type dye-sensitized solar cells - Dini, Danilo; Halpin, Yvonne; Vos, Johannes G.; Gibson, Elizabeth A. (Coordination chemistry reviews, 2015)
A range of preparation methods for p-type NiO electrodes are reported together with associated DSC cell parameters and electrochemical details. •Discussion of effect of preparation method of NiO thin layers on the structural features of NiO modified electrodes.•Discussion of effect of preparation method of NiO thin layers on their DSC parameters.•Discussion of effect of preparation method of NiO thin layers on the electrochemical properties. Improving the efficiency of p-type dye-sensitized solar cells (DSCs) is an important part of the development of high performance tandem DSCs. The optimization of the conversion efficiency of p-DSCs could make a considerable contribution in the improvement of solar cells at a molecular level. Nickel oxide is the most widely used material in p-DSCs, due to its ease of preparation, chemical and structural stability, and electrical properties. However, improvement of the quality and conductivity of NiO based photocathodes needs to be achieved to bring further improvements to the solar cell efficiency. The subject of this review is to consider the effect of the preparation of NiO surfaces on their efficiency as photocathodes.